2002
DOI: 10.1046/j.0007-1323.2001.01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of antireflux surgery indicate the need for a randomized clinical trial

Abstract: This study does not support the presumption that laparoscopic antireflux surgery is to be preferred to the open procedure. It is strongly recommended that a randomized controlled trial be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
1
23
3
1
Order By: Relevance
“…Recent retrospective analyses comparing open and laparoscopic antireflux procedures suggested that the open technique results in better symptomatic control than the laparoscopic [3,33], with recurrence rates of 29% after laparoscopy. These authors advocated prospective trials comparing open and laparoscopic approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent retrospective analyses comparing open and laparoscopic antireflux procedures suggested that the open technique results in better symptomatic control than the laparoscopic [3,33], with recurrence rates of 29% after laparoscopy. These authors advocated prospective trials comparing open and laparoscopic approach.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the surgical treatment for GERD, and in particular the use of the laparoscopic technique for GERD, have been questioned,. The criticism is either based on retrospective reports of high rates of symptomatic recurrence [3], increased rates of postoperative dysphagia after Nissen procedures [4], or high rates of postoperative use of antireflux medication [5].…”
mentioning
confidence: 99%
“…36 The majority of authors agree that the main reasons for failures are technical errors in the performance of surgery such as asymmetric wrap, early disruption, wrap migration, and slipped fundoplication producing abnormal deformities, clearly demonstrated by radiologic and endoscopic assessment. [37][38][39][40][41][42] The recurrence rate of erosive esophagitis resulting from failure of antireflux operation ranges from 3% to 16%, most of them caused by a misperformed surgical procedure with a high proportion of positive acid reflux tests after the operation. 23 Mickevicius et al 43 suggests that a wrap length is important in fundoplication in order to avoid postsurgical failures.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42] The recurrence rate of erosive esophagitis resulting from failure of antireflux operation ranges from 3% to 16%, most of them caused by a misperformed surgical procedure with a high proportion of positive acid reflux tests after the operation.…”
mentioning
confidence: 99%
“…After a posterior partial fundoplication, however, gas insufflation into the stomach seldom elicits TLESRs, but it is slightly more commonly after a total fundoplication. More importantly when a TLESR occurs after a partial wrap, it is associated with a lower nadir pressure in the LES; a larger number of common cavities suggestive of a better restored ability to vent air from the stomach compared to those having a total fundoplication [98,[110][111][112][113][114][115]. …”
Section: Lower Esophageal Sphincter Functionmentioning
confidence: 99%